2015
DOI: 10.1021/es505078r
|View full text |Cite
|
Sign up to set email alerts
|

Determining High-Quality Critical Body Residues for Multiple Species and Chemicals by Applying Improved Experimental Design and Data Interpretation Concepts

Abstract: Ecotoxicological effect data are generally expressed as effective concentrations in the external exposure medium and do thus not account for differences in chemical uptake, bioavailability, and metabolism, which can introduce substantial data variation. The Critical Body Residue (CBR) concept provides clear advantages, because it links effects directly to the internal exposure. Using CBRs instead of external concentrations should therefore reduce variability. For compounds that act via narcosis even a constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…CBRs are expected to be similar (in the range of 2-8 mmol/kg) among baseline toxicants and small aquatic organisms due to similar mode of action (Van Wezel and Opperhuizen, 1995). Recently, van der Heijden et al (2015) showed that CBR values for seven narcotics tested in three species ranged from 2.1 to 16.1 mmol/kg fresh wt. McCarty et al (2013) reviewed a large set of CBR values and reported a mean CBR of 1.80 mmol/kg fresh wt for 29 narcotics in algae, invertebrates and fish.…”
Section: Effect Values Were Within Ranges Expected For Baseline Toxicitymentioning
confidence: 99%
“…CBRs are expected to be similar (in the range of 2-8 mmol/kg) among baseline toxicants and small aquatic organisms due to similar mode of action (Van Wezel and Opperhuizen, 1995). Recently, van der Heijden et al (2015) showed that CBR values for seven narcotics tested in three species ranged from 2.1 to 16.1 mmol/kg fresh wt. McCarty et al (2013) reviewed a large set of CBR values and reported a mean CBR of 1.80 mmol/kg fresh wt for 29 narcotics in algae, invertebrates and fish.…”
Section: Effect Values Were Within Ranges Expected For Baseline Toxicitymentioning
confidence: 99%
“…The estimated solubilities in octanol ( S O ) range from 1900 mol m −3 to 2800 mol m −3 for the first 5 chemicals, but a much larger value of 91,700 mol m −3 apparently applies to 4‐Cl‐3‐MP because of the high solubility in water. van der Heijden et al give a lower value of S W by a factor of 2, which still gives a very high value of S O . This high solubility in water is reflected in a very low ILA.…”
Section: Illustrationmentioning
confidence: 97%
“… Values for log K OW and S W were taken from Mackay et al if available; otherwise EPISuite was used. Values for lipid content ( L ) and CBR are from van der Heijden et al . Values for k 1 , k 2 , ILC, and ILA were calculated for each guppy trial reported by van der Heijden et al , and then an average value was calculated for each chemical (including low, medium, and high concentrations) and reported in this table.…”
Section: Illustrationmentioning
confidence: 99%
See 2 more Smart Citations